1989
DOI: 10.1159/000125176
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Activates Tuberoinfundibular Dopamine Neurons and Increases Serum Corticosterone Concentrations in the Rat

Abstract: The activity of tuberoinfundibular dopamine neurons, as estimated from the amount of dihydroxyphenylalanine (DOPA) formed in the median eminence after the inhibition of DOPA decarboxylase and the concentration of dihydroxyphenyl-acetic acid (DOPAC) in this brain region, was significantly increased 1–8 h following the intracerebroventricular (i.c.v.) administration of neurotensin (20 µg). Neurotensin (5 and 20 µg i.c.v.) also significantly increased DOPAC concentrations in the n. accumbens but had no effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…neurotensin NT 1 receptor and neurotensin NT 2 receptor) in the hypothalamus and the central nucleus of the amygdala suggests a central role in the regulation of endocrine responses to external events or in the alteration of emotional tone, functions thought to be controlled by the amygdala (Roberts et al, 1982;Elde et al, 1990;Sarret et al, 1998;Walker et al, 1998). Central administration of neurotensin was reported to increase plasma levels of ACTH and corticosterone (Gudelsky et al, 1989;Nicot et al, 1994;Nicot et al, 1997). Psychological stressors, such as non-escapable tail electric shock in rats, were found to increase neurotensin mRNA within the medial parvocellular region of the paraventricular nucleus of the hypothalamus (Helmreich et al, 1999).…”
Section: Effect Of the Neurotensin Receptor Antagonist Sr48692 In Thementioning
confidence: 99%
“…neurotensin NT 1 receptor and neurotensin NT 2 receptor) in the hypothalamus and the central nucleus of the amygdala suggests a central role in the regulation of endocrine responses to external events or in the alteration of emotional tone, functions thought to be controlled by the amygdala (Roberts et al, 1982;Elde et al, 1990;Sarret et al, 1998;Walker et al, 1998). Central administration of neurotensin was reported to increase plasma levels of ACTH and corticosterone (Gudelsky et al, 1989;Nicot et al, 1994;Nicot et al, 1997). Psychological stressors, such as non-escapable tail electric shock in rats, were found to increase neurotensin mRNA within the medial parvocellular region of the paraventricular nucleus of the hypothalamus (Helmreich et al, 1999).…”
Section: Effect Of the Neurotensin Receptor Antagonist Sr48692 In Thementioning
confidence: 99%
“…An interaction between glucocorticoids and NT in modulating the behavioral response to cocaine is suggested by the effects of this peptide on the HPA axis. Central injection of NT stimulates the release of ACTH and corticosterone (Gudelsky et al 1989;Nicot et al 1994). Moreover, chronic administration of SR 48692 at the level of the paraventricular nucleus of the hypothalamus decreases the circadian rise of ACTH and corticosterone plasma levels during the evening, as well as the increase in both hormones after exposure to stress Rowe et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…For example, central administration of NT in freely moving rats stimulates release of adrenocorticotropin hormone and corticosterone levels (16)(17)(18), indicating that it may be involved in the regulation of hypothalamic-pituitary-adrenal axis activity. Ceccatelli et al also showed up-regulation of the NT precursor mRNA in the paraventricular nucleus of the hypothalamus after immobilization stress (19).…”
mentioning
confidence: 99%